1980
DOI: 10.1126/science.6254143
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-Induced Alteration in Sedimentation Behavior of Membrane Bound β-Adrenergic Receptors

Abstract: Incubation of astrocytoma cells with catecholamines results in a decrease in catecholamine-stimulated adenylate cyclase activity and a concomitant alteration in the sedimentation properties of particulate beta-adrenergic receptors. The altered receptors exhibit agonist binding properties similar to those of receptors that are "uncoupled" from adenylate cyclase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
2

Year Published

1982
1982
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(56 citation statements)
references
References 20 publications
1
52
0
2
Order By: Relevance
“…The notion that an early uncoupling of the receptor from adenylyl cyclase activation, which precedes the sequestration, contributes to the loss of hormonal respon siveness has emerged in the last few years. Harden et al (1980) demon strated that in human astrocytoma cells the appearance of receptors in the light vesicle fraction (sequestration) was delayed '" 1 min relative to the rapid agonist-induced decrease in adenylyl cyclase hormonal respon siveness. Moreover, blockade of receptor sequestration by pretreatment of the cells with concanavalin A or by incubation at 4°C (Homburger et al 1980) failed to prevent desensitization.…”
Section: Functional Uncoupling I Sequestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that an early uncoupling of the receptor from adenylyl cyclase activation, which precedes the sequestration, contributes to the loss of hormonal respon siveness has emerged in the last few years. Harden et al (1980) demon strated that in human astrocytoma cells the appearance of receptors in the light vesicle fraction (sequestration) was delayed '" 1 min relative to the rapid agonist-induced decrease in adenylyl cyclase hormonal respon siveness. Moreover, blockade of receptor sequestration by pretreatment of the cells with concanavalin A or by incubation at 4°C (Homburger et al 1980) failed to prevent desensitization.…”
Section: Functional Uncoupling I Sequestrationmentioning
confidence: 99%
“…Stadel et al (1983b) further documented that these cytosolic receptors are associated with a light membrane fraction. In mammalian cells, Harden et al (1980) demon strated that pretreatment with isoproterenol promoted the sequestra tion of a signifi cant portion of the p-adrenergic receptors from a heavy membrane fraction to a light membrane fraction (light vesicle) on sucrose gradients.…”
Section: Functional Uncoupling I Sequestrationmentioning
confidence: 99%
“…membrane control. The cells have adrenergic @-receptors [8], Ai-adenosine receptors 191, muscarinic receptors [lo], Hi-histamine receptors [ll], bradykinin receptors [12] and thromboxane A2 receptors [13]. Phosphoinositide hydrolysis induced by stimulations of muscarinic, Ha-histamine, bradykinin and thromboxane A2 receptors is dependent on GTP, but resistant to IAP treatment [11,13-151, meaning that a G-protein involved in phospholipase C activation is not a substrate for IAP in human astrocytoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Harden et al (5) have demonstrated that parallel to the densensitization of the adenylate cyclase, in addition to plasma membrane receptors, a second, physically separable receptor population appeared. This second receptor population occurred in a vesicular receptor fraction while at the same time the number of receptors bound to the plasma membrane fraction was reduced.…”
mentioning
confidence: 99%
“…Therefore, [3H]CGP-12177 is a tool to measure in intact cells (8) the agonist-induced disappearance of cell surface receptors, which has been demonstrated before by Harden et al (5) after lysing the cells. Using this ligand, it has been demonstrated recently that the disappearance of B-adrenergic receptors is transient and is followed by a fast reappearance of receptors after removal of the agonist (8).…”
mentioning
confidence: 99%